2021
DOI: 10.3390/atmos12040423
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Contribution of Different Particulate Matter Sources on Pollution in Sofia City

Abstract: The habitants of Sofia, the capital city of Bulgaria, are unfortunately exposed to high levels of particulate matter (PM), despite a lot of efforts made by the government and the municipality in recent decades. A high resolution model using the Atmospheric Dispersion Modeling System (ADMS)-Urban was carried out for one year (2014) with elevated levels of PM concentration for the Sofia region measured during the winter. Four main emission sources (point industrial, domestic heating, roads, and unorganized trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…A recent study for Sofia, based on the Positive Matrix Factorization (PMF) receptor model for source contribution of different groups of emission sources to PM 10 concentrations [10], indicated 23% for biomass burning and 9% for transport on an annual basis for 2019. Another recent study on the determination of the local pollution of PM and PAH in the Sofia municipality by the Gaussian dispersion-based ADMS-Urban model showed that domestic heating contributed 59% of the PM 2.5 concentrations [48].…”
Section: Pm25 and Bc Emissionsmentioning
confidence: 99%
“…A recent study for Sofia, based on the Positive Matrix Factorization (PMF) receptor model for source contribution of different groups of emission sources to PM 10 concentrations [10], indicated 23% for biomass burning and 9% for transport on an annual basis for 2019. Another recent study on the determination of the local pollution of PM and PAH in the Sofia municipality by the Gaussian dispersion-based ADMS-Urban model showed that domestic heating contributed 59% of the PM 2.5 concentrations [48].…”
Section: Pm25 and Bc Emissionsmentioning
confidence: 99%
“…Large floods and drought periods have increasingly taken place in the Upper Iskar Basin in the region of Sofia (Daniell 2011). PM10 concentrations in Bulgaria were one of the highest in 2009 and it continues to be the aforesaid nowadays (Dimitrova & Velizarova 2021). PM is particularly harmful during the winter period in big cities, such as Sofia, being domestic heating and transport emissions the main sources.…”
Section: Sofia Case Studymentioning
confidence: 99%
“…The aim of our study investigating the relationship between daily air pollution levels and hospital admissions for ischaemic heart disease, cerebrovascular accidents, and diabetes mellitus in Sofia, Bulgaria, was to expand its scope by including 10 years worth of data on hospital admissions and air quality, using multivariate analysis techniques suitable for modelling autocorrelated count data. Sofia is the capital city of Bulgaria characterised by high population density, heavy traffic, and heavy use of fossil fuel for household heating, coupled with poor ventilation and temperature inversions due to its location in a mountain basin ( 17 , 22 ).…”
mentioning
confidence: 99%